Investigating the fine milling of pigment in a colourant formulation on the Bühler PML2 Superflow mill - Lewis, Emily (Department of Chemical Engineering, 2022)
Stirred media mills remain the most suitable option in the coatings industry for the ultrafine grinding of colourants. The fineness of grind and colourant tint strength are typically used as indicators for the end of a production run during colourant manufacturing. These typical parameters from the coatings industry make it difficult to recognise whether the end point of a production run to maximise the product yield has actually been reached, without excessive time or energy. Including particle size analysis, to enable the analysis of energy efficiency and production performance, could assist to understand the impact of the various milling parameters. This study compares the various experimental approaches that can be taken to understand milling performances during colourant production. A laboratory scale, Bühler Superflow, vertical, stirred media mill is used, with a yellow lead (II) chromate colourant. The milling parameters reviewed included rotor tip speed, the media filling level, the media size and solid content of the colourant suspension. A three-level factorial design of experiments was used for each parameter. The results are analysed in terms of the Kwade stress model and the one factor at a time approach, as well as a response surface study. The significant interaction effects (ie, p-value < 0.5) identified using the response surface study included the tip speed / media size (AC) and media filling level / media size (BC) interaction terms for both the energy efficiency and rate models. For the power model, the tip speed / media filling level (AB) and tip speed / solids content of the colourant suspension (AD) interaction terms were deemed significant. This confirmation disqualified the one factor at a time method as a viable means to determine optimal milling performance. The results did, however, confirm the validity of the stress energy model as a minimum stress energy of 0.067x10-3Nm was identifiable across the different specific energy input levels. This methodology would be most useful for future colourant production optimisation studies. As part of the model validation, the higher stirrer tip speed of 7.3m/s, higher solids content of 55wt% and lower media size of 0.8mm paired with a mid-level media filling level of 87% was identified as the optimal combination of parameters to maximise the production rate and energy efficiency.